Contribution à l'étude comparative de l'effet du seuil à parois mince et épaisse sur les caractéristiques du ressaut hydraulique dans le canal rectangulaire de section composée - جمال الدين, اللبي; سعد الدين, حمدة; أحمد, قريشة (University of El-Oued, 2021)
"Our contribution proposes to the study of the effect of the hydraulic jump evolves in rectangular channel abruptly widened with the characteristics of the flow. To this end, our study research is subdivided into two main parts, the first concerning a bibliographic study citing the works that are related to our proposed theme and the second part of our work plan is to establish dimensionless relations with general characteristics. to size the ancillary works. ""تتمثل مساهمتنا في دراسة تأثير العتبة ذات السمك الرقيق والسميك على خصائص القفزة الهيدروليكية التي تتطور داخل قناة مركبة الشكل. تحقيقًا لهذه الغاية ، ينقسم بحثنا الدراسي إلى جزأين رئيسيين ، الأول يتعلق بدراسة ببليوغرافية تستشهد بالأعمال المتعلقة بموضوعنا المقترح والجزء الثاني من خطة عملنا هو ايجاد علاقات دون أبعاد ذات طابع عام تسمح بتحديد أبعاد الهياكل الإضافية لمنشئات الري. "
Conception et diagnostic du système d'AEP et d'Assainissement- مذكرة ماستر تخصص
Keywords: Hydraulic jump, Rectangular canal of compound section, characterization of the hydraulic jump.; القفزة الهيدروليكية, العتمة الرقيقة، العتمة لخشنة، قناة مستطيلة ذات مقطع مركب، ميزة القفزة الهيدروليكية.